Zn(II) PRECONCENTRATED WITH CATION EXCHANGER PS-DVB-SO3H WITH pH CONTROL AND ELUID RECOVERY ANALYSIS WITH ATOMIC ABSORPTION (EAAF) - Cjuno H., J. (2012)
The objective of this study is to propose a method of pre-concentration aqueous samples directly Zn (II) with a commercial cation exchange resin of the type PS-DVB-SO3H strongly acidic Ionac ® C-249. It should be noted that the analysis of Zn atomic absorption flame detector (EAAF) is limited in the sub-ppm levels or ultratrace. For this purpose, we used solutions of Zn (II) to 0.01 ppm (pH = 6.20) were added to which fixed amounts exchanger on a volume of each solution. In exchange, defined residence times, speed of agitation and pH variation with time. Once reached the maximum time, samples were taken for the analysis solution and exchanger EAAF was treated with acid to elute the Zn exchanged and further analysis. The results showed that elution with 6N HCl, gave recoveries between 93 to 96% and pH monitoring function of time possible to monitor the endpoint exchange even with highly diluted samples.